Diagnostic Value of Helicobacter Pylori Serologic Test in Pediatric Population with Abdominal Pain - Shohreh Maleknejad; Afshin Safaei; Mohammadreza Ahmadi (Acta Medica Iranica, 2010)
the aim of this study was to determine the diagnostic value of a serologic test for Helicobacter pylori (H. pylori) in pediatric population presenting with abdominal pain suspected of peptic disease. We conducted a preospective cross sectional study. There were 202 children with abdominal pain. Serologic BM test using Helisual Quick test kit was performed. All patients then underwent endoscopic examination. The calculated sensitivity, specificity, positive and negative predictive values of the applied serologic BM test were 72.4%, 64.8%, 44.6% and 85.7%, respectively. We concluded that a positive result from serologic test could not be judged independently. Thus, in symptomatic patients, other diagnostic methods (e.g. endoscopy and UBT) should be applied prior to the therapeutic decisions.